Oronasal Fistula Incidence Associated With Vomer Flap Repair of Cleft Palate: A Systematic Review and Meta-Analysis. (August 2021) - Vandenberg, Katherine; Castle, Michael; Qeadan, Fares; Kraai, Tania
Objectives: To determine the incidence of oronasal fistulas (ONF) associated with primary repair of the anterior palate using a single-layered, superiorly based, vomer mucoperiosteal flap. Design: A systematic review of MEDLINE, PubMed, Cochrane, and Web of Science databases using the keywords: "vomer flap" and "cleft palate repair" were carried out. A meta-analysis was performed using random effect modeling with stratified analysis by syndromic diagnosis, number of surgeons, and mean age. Main Outcome Measure(s): Incidence of ONFs. Results: The meta-analysis included 9 studies with a total of 464 children who met inclusion criteria. The overall ONF rate was 3.0% (95% CI: 1.0-9.0). Fistula rates were not significantly different in studies that included syndromic patients compared to studies that did not, 5.0% (95% CI: 1.0-24.0) versus 3.0% (95% CI: 1.0-6.0), respectively. There was no significant difference between studies in which there was a single surgeon versus multiple surgeons, 3.0% (95% CI: 1.0-13.0) versus 4.0% (95% CI: 1.0-8.0), respectively. Age at the time of cleft repair showed no statistically significant difference in fistula rate when comparing children with a mean age less than 12 months to those greater than 12 months, 3.0% (95% CI: 1.0-5.0) versus 5.0% (95% CI: 1.0-28.0), respectively. Conclusions: The vomer flap technique in cleft palate repair appears to be associated with a low ONF rate unaffected by syndromic diagnosis, number of surgeons, or patient age at time of repair.